Detection of Prostate Cancer Biomarker PCA3 by Using Aptasensors - Crulhas, Bruno P. [UNESP]; Basso, Caroline R. [UNESP]; Castro, Gustavo R. [UNESP]; Pedrosa, Valber A. [UNESP] (Bentham Science Publishers, 2022)
Background: Prostate cancer cells have very high PCA3 messenger RNA lev-els, which turns them into one of the new biomarkers for prostate cancer prognosis and di-agnosis. Objective: Our goal here is to develop a new aptasensor to detect PCA3 release by the cancer cell. Methods: DNA hairpin containing PCA3 aptamer was thiolated, conjugated to methy-lene blue (MB) redox probe, and immobilized on gold electrode through self-assembly to detect label-free cancer cells. Results: Our data have evidenced stable and sensitive sensors presenting a wide linear detection range (0-150ng/mL). In addition, monitoring PCA3 released by different types of prostate cells can provide in-depth knowledge about prostate cancer dynamics; therefore, it is a powerful platform for earlier clinical diagnostic. The released PCA3 can vary de-pending on the type of adopted prostate cells. Conclusion: PCA3 release was monitored in a group of cells for 2 h; it showed signifi-cantly higher expression in both LNCaP and PC-3 cells. This strategy provides a unique and simple methodology to achieve more sensitive and specific PCA3 detection; thus, it emerged as a promising tool for early cost-effective diagnosis.
Keywords: aptamer; Aptasensor; biomarker; cancer cell; PCA3; releasing protein